270. Prevalence and Impact of β-Lactam Allergies at a Canadian Pediatric Center. (26th November 2018) - Wong, Jacqueline; Torres, Mariana; Timberlake, Kathryn; Atkinson, Adelle; Science, Michelle
Abstract: Background: Rational and appropriate use of antibiotics is a global priority since inappropriate or unnecessary use is associated with antibiotic resistance and patient morbidity. In adult patients, the presence of a β-lactam allergy label (BLA) often leads to the use of broader spectrum agents with more toxicity. Infections account for a majority of pediatric hospital admissions, and β-lactam antibiotics are often considered first-line therapy. There is limited evidence on the impact of BLA on prescribing practices in pediatrics. The primary objective of this study was to determine the proportion of children with a reported BLA who received second-line antimicrobials (as determined by hospital empiric antibiotic guidelines). The secondary objective was to identify patient characteristics associated with receiving second-line antibiotics. Methods: A 1-year retrospective cohort study was undertaken at the Hospital for Sick Children. We reviewed the characteristics and management of patients with a reported BLA who received antibiotics from January to December 2016. Results: Of the 16, 224 admissions in 2016, 206 patients with a reported BLA received antibiotics. Among these patients, the median age was 7.9 years (IQR 4.0, 12.8) and the majority of patients had at least one medical condition ( n = 120, 59.3%), including 27 children with complex medical or genetic conditions (13.1%). Penicillin ( n = 86, 41.8%) and amoxicillin ( n = 70, 33.9%) were the most commonly reported allergens. Nonsevere rashes were the most commonly reported allergic reactions ( n = 158, 73.1%). Ninety-four patients (46%; 95% CI (0.39, 0.52) received second-line therapy. After adjusting for age and sex, the odds of receiving a second-line antibiotic were increased in patients with any underlying medical condition (OR = 2.45, 95% CI 1.32–4.56), had a reported allergic reaction that was deemed high-risk (i.e., anaphylaxis, respiratory or systemic symptoms, severe rashes) (OR = 2.61, 95% CI 1.11–6.11) or who received antibiotics for surgical prophylaxis (OR = 3.30, 95% CI 1.44–7.54). Conclusion: Almost half of pediatric patients with a reported BLA received a second-line antibiotic when compared with hospital empiric antibiotic guidelines. There is a need for a systematic approach to evaluating reported BLA in order to promote judicious prescribing habits. Disclosures: All authors: No reported disclosures.